Prevalence of Extended-Spectrum Beta-Lactamases in producing Escherichia coli in beef sold in traditional markets in Surabaya, Indonesia - Dhandy Koesoemo Wardhana; DEVI AYU SAFITRI; SUWAIBATUL ANNISA; NENNY HARIJANI; AGNES THERESIA SOELIH ESTOEPANGESTIE; LAILATUL MAGHFIROH (Society for Indonesian Biodiversity, 2021)
Abstract. Wardhana DK, Safitri DA, Anisa S, Harijani N, Estoepangestie S, Maghfiroh L. 2021. Prevalence of Extended-Spectrum Beta-Lactamases in producing Escherichia coli in beef sold in traditional markets in Surabaya, Indonesia. Biodiversitas 22: 2789-2793. Meat is a source of protein, but it can be contaminated by microorganisms such as Escherichia coli (E. coli). Some species of E. coli become resistant to antibiotics and produce Extended-Spectrum Beta-Lactamase (ESBL) that limit the choice of antibiotics for treatment of E. coli infection. The purpose of the study was to investigate the prevalence of ESBLs leading to the growth of Escherichia coli (E. coli) in beef sold in local markets in Surabaya City, Indonesia. A total of 60 samples from 10 traditional markets were tested. Isolated and identified E. coli strains were examined to detect the ESBL production through four-disc diffusion tests using cefotaxime (30 ?g), ceftazidime (30 ?g), ceftriaxone (30 ?g), and aztreonam (30 ?g). Then, the minimum inhibitory concentration was measured. The study showed the presence of ESBL-producing E. coli in beef sold in the traditional markets in Surabaya. The average E. coli concentration in the beef was at 43.3%, and the highest resistance of the isolates was observed for cefotaxime (46.1%), ceftazidime (23.1%) ceftriaxone (19.2%), and aztreonam (38.4%). Data of ESBL-producing E. coli in broiler chicken meat in the traditional markets showed all of the E. coli isolates were resistant to ampicillin, while 48.4% of them were resistant to, cephazolin. Only few (13%) were resistant to ceftazidime, and few others (9.6%) showed resistance to cefotaxime. The least number of them (6.4%) were resistant to ceftriaxone, and most of them were resistant to tetracycline (87.2%). Therefore, ESBLs were not reported producing E. coli in the beef. The presence of ESBL-producing E. coli in the beef gives an alert that good hygiene practices should be applied to handle meat safety and control the use of antibiotics